Characteristics of the psychophysical state of primary school-aged children with autism spectrum disorders - Demianov , Vitalii; Kovtun , Alla (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. Physical education is considered one of the important forms of improving the psycho-physical condition of primary school-aged children with autism spectrum disorders. Until recently, children with autism were not classified as a separate category for adaptive physical education. Consequently, there is currently no system of corrective and educational physical education aimed at improving their psycho-physical condition. The hypothesis of the study is that the analysis of modern data on the psychophysical condition of primary school children with autism spectrum disorders will allow the identification of the main areas for improving their physical education. The purpose of the study – identify the peculiarities of the psychophysical state of primary school children with autism spectrum disorders in order to improve the process of adaptive physical education. Materials and methods. The research was conducted at the Prydniprovsk State Academy of Physical Culture and Sport. During the research process, methods of analysis, systematization, and generalization of scientific, methodological, and special literature were used. Results. The peculiarities of autism manifestations, the level of decrease in psychophysical condition indicators, and other individual characteristics of children with autism spectrum disorders can vary in combinations and degrees of severity. Impaired social communication in children with autism spectrum disorders leads to reduced motor activity, and low physical activity provokes a low level of physical fitness and disharmony in physical development. Movement disorders, in turn, hinder the child’s normal speech development, mastery of writing skills, building household skills, and engaging in play activities. Conclusion. The analysis of data from scientific and methodological literature showed the need for a comprehensive study of various groups of indicators of the psychophysical state of younger schoolchildren with autism spectrum disorders, namely physical, cognitive, behavioral, and communicative indicators. This will allow for etablishing possible relationships between these indicators and determining directions for improving physical education in general secondary education institutions for children with autism.